Peach chilling injury for different conservation conditions - Rodrigues, Cristina (2019)
The scientific name Prunuspersica emerged from a European belief, originating from Persia, however this fruit a rose and was first cultivated in China. It was introduced in Europeat the beginning of the Romaner a and emerged in the United States of America(USA) during the 19th century(Campbell,2004).